Conspicuous eggs and colourful hypotheses: testing the role of multiple influences on avian eggshell appearance. (20th December 2011) - Cassey, Phillip; Maurer, Golo; Lovell, P. George; Hanley, Daniel
The diversity of eggshell colours and patterning across different birds is a fascinating example of the extended avian phenotype. The avian egg's background colours range from light green/yellow to brilliant blue and intense maroon, and with the scrawling patterns comparable to the assortment of eggs found in an Easter Bunny's basket. Here we briefly introduce the diversity of eggshell appearance, its perplexingly narrow chemical basis, and clarify how the a priori assessment of assumptions and potential hypotheses can shape new eggshell research. In addition, we highlight some of the recent hypotheses developed outside the visual paradigm that has dictated the most influential hypotheses of eggshell appearance to date. Finally, we indicate priority areas for future comprehensive research on eggshells based on adaptations to ongoing changes in environmental conditions.